2006
DOI: 10.1007/s11199-006-9031-1
|View full text |Cite
|
Sign up to set email alerts
|

Rape Myths and Social Distance Toward Sex Offenders and Victims among Therapists and Students

Abstract: This study was designed to investigate the relationships between gender role stereotypes, rape myths, and social distance from sex offenders and sex crime victims among students and therapists. A Rape Myth Acceptance Scale, an Attitude Variables Questionnaire, and a Social Distance Scale were administered to 125 female social science students and 51 female therapists. The findings validated our hypothesis: traditional gender role attitudes and belief in rape myths were positively related to social distance. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
2
48
2
Order By: Relevance
“…Meanwhile, very rarely is there any discussion at all about male victimization. Attitudes and beliefs about rape appear to be deeply woven into the culture, are complex, and are extremely resistant to change (Shechory & Idisis, 2006). Although research has consistently demonstrated the adverse impact of rape myths in survivors' interactions with a range of service providers (e.g., Ullman & Townsend, 2007), comparatively little is known about specific mechanisms that lead to the acceptance of rape myths.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, very rarely is there any discussion at all about male victimization. Attitudes and beliefs about rape appear to be deeply woven into the culture, are complex, and are extremely resistant to change (Shechory & Idisis, 2006). Although research has consistently demonstrated the adverse impact of rape myths in survivors' interactions with a range of service providers (e.g., Ullman & Townsend, 2007), comparatively little is known about specific mechanisms that lead to the acceptance of rape myths.…”
Section: Discussionmentioning
confidence: 99%
“…Aosved and Long 2006). Research finds that men tend to believe more strongly in rape myths than women (Lonsway and Fitzgerald 1994;Shechory and Idisis 2006) and this may translate into gender differences in intervention responsibility.…”
Section: Gender and Sexual Assault Bystander Interventionmentioning
confidence: 99%
“…Alternatively, exonerees may be stigmatized because they are perceived as victims. For example, Shechory and Idisis (2006) observed that participants desired greater social distance from innocent victims of crime. Thus, participants may stigmatize exonerees because they were victims of the criminal justice system (see Westervelt & Cook, 2009).…”
Section: Limitations and Future Researchmentioning
confidence: 99%